Navigating change: agile leadership implementation in local government of Palu City - Sary, Chichi Kumala; Adda, Harnida Wahyuni; Rossanti, Niluh Putu Evvy (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
This research investigates the implementation of agile leadership within the Palu City government, adopting a constructivist paradigm with a qualitative approach. Data collection was carried out by interviews with seven informants. Data were collected and analyzed using triangulation techniques and MAXQDA-20 software. The findings reveal that the Palu City government successfully integrates agile leadership principles such as adaptability, stakeholder involvement, transparency, and innovation. Notably, these practices have facilitated effective policy implementation, notably in waste management and urban planning, resulting in the attainment of the Adipura Award. Despite challenges posed by natural disasters and pandemics, the government's agile approach has enabled it to effectively navigate crises and maintain service delivery standards. The study underscores the significance of transitioning from traditional